Rancangan Kapasitas Tangki Penyimpanan Udara Instrumen Pada Pabrik - Dinda Rizka Fadhillah; Sry Wahyuni; Lely Pramesti (JURNAL VOKASI TEKNIK, 2024)
The instrument air receiver plays a role in keeping the process in the factory running. The instrument air receiver is provided to supply the air needs for the operation of instrument equipment in the factory if there is a problem with the instrument air supply system. Before keeping in the instrument air receiver, instrument air is fed into several tools to be processed, including a filter, compressor, and dryer. This study was conducted to calculate the capacity of the instrument air receiver if the required instrument air flow rate is 70 Nm3/h. The receiver is designed with a residence time of 15 minutes and a maximum tank operating pressure of 9 barg to 5.5 barg. In calculating the receiver capacity, the flow rate is usually given a margin of 10% so that the working capacity of instrument air is 6 m3.